Enhancing knowledge and well-being through leisure reading to promote cognitive, emotional, and social benefits for overall personal growth - Dwi Diva A. Panjaitan; Majid Wajdi; I Putu Yoga Laksana; Zanyar Nathir Ghafar; Md. Abdur Rouf; Omar Mohammad-Ameen Ahmad Hazaymeh (Yayasan Mitra Persada Nusantara, 2026)
This study aims to explore the multifaceted benefits of reading during free time, focusing on its impact on knowledge acquisition, emotional well-being, and social development. A mixed-methods approach was employed, combining surveys and focus groups across diverse age groups including adolescents and young adults. Data analysis revealed that leisure reading enhances vocabulary, literacy skills, and critical thinking while also providing relaxation, stress relief, and emotional support. Additionally, reading for pleasure fosters empathy, cultural competence, and ethical reflection, particularly among medical students and youth. The findings highlight the role of accessible resources such as public libraries in promoting leisure reading and suggest that early exposure to books encourages lifelong reading habits. The study concludes that leisure reading is a vital activity for intellectual growth and psychological health, recommending further longitudinal research to deepen understanding of its long-term effects.